The Correlation Between Student Motivation and Their Learning English Achievement at SMP Negeri 4 Tondano - Violeta Rongkonusa; Liando, Nihta V. F; Wungow, Trully (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
One of the most crucial factors for improved success in studying English is motivation. This study's objective is to determine the motivation of students to learn English and the relationship between the learning and motivation of students. English proficiency at SMPN 4 Tondano in the study of English. The author gathered information from the questionnaire and supporting documents, then used the correlation coefficient of Pearson's product moment (SPSS 0.20) and questionnaire percentages to analyze the data. Thirty-one junior high school students from Tondano's second grade participated in this study. The sample was obtained by the writer using random sampling. The study's conclusions state that there were 31 participants. According to the survey results, 0% of students lackted motivation, 0% had moderate motivation, 64.5% had great motivation, and 35.5% had very high motivation. The average motivation score for all students at SMPN 4 Tondano is 64.09, meaning that most of them, especially those in the second grade, have very high motivation. The correlation coefficient the connection between pupils' motivation and their ability in English studies is 0.573, falling into the third category (0.40-0.70) That enough correlation exists between the X and Y variables. Put another way, this indicates that there is a strong enough relationship between pupils' motivation and their success in learning English. The result shows that the two variables (X and Y) have a positive association.